Mengatasi Kecemasan Karir Melalui Konseling Kelompok Eksistensial - Abdi, Sofyan; Hasna, Afra; Sofyan, Annisa Amalia; Chairunnisa, Chairunnisa; Fitriani, Desy; Azlya, Shasya; Chintia, Dhea Nada (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2024)
This study aims to assist students at SMK Al-Wathoniyyah in reducing anxiety when choosing a career path after completing vocational secondary education through group counseling services with an existential humanistic approach. High anxiety about career choices, such as deciding between pursuing a desired college major or working in line with their passion, is a common issue faced by high school or vocational students, typically aged 15-18, who are still in their adolescent developmental stage. This research uses a qualitative method with a population of 5 twelfth-grade students and 2 students as the research sample. The instrument used in this study is an interview, followed by a treatment in the form of group counseling services with an existential humanistic approach. Group counseling services with an existential humanistic approach are effective in reducing students' anxiety in career decision-making.